Modifications of soil chemical composition and maize plant early growth caused by addition of lime and phosphate fertilizers on the soil surface - Ernani, Paulo Roberto; Steckling, Cleiton; Bayer, Cimélio (Revista de Ciências Agroveterinárias, 2006)
Despite the small mobility of phosphates and liming, addition of these materials on the soil surface, without incorporation, has often increased crop yield. However, it is unknown the behavior of plant roots developed in a soil with only a thin layer chemically ameliorated, as well as the result of combining large amounts of lime and phosphates on P availability. This study was carried out to evaluate the effect of surface addition of lime and phosphates on maize dry mattert yield as well as on some soil and root parameters. Lime rates applied on the soil surface were equivalents to 0, 1/8, 1/4 e 1/2 of the quantity required to raise the pH-H2O of a 17 cm soil layer depth to 6.0 (5.0 g kg-1), which was also added but incorporated into the soil. Phosphorus was applied at rate of 100 mg P kg-1, as diammonium phosphate (DAP) or triple superphosphate (TSF). The experiment was set in a greenhouse using pots containing 5.0 kg (dry base) of an acid Oxisol where five maize plants were grown for 26 days after emergence. Addition of lime on the soil surface improved the chemical characteristics of the most superficial soil layer (0 to 2.5 cm). Increases on maize dry matter yield due to surface liming occurred only with the smallest lime rate, which had the same efficiency of the integral rate incorporated into the soil. Liming increased P uptake regardless of rates applied or forms of addition, but had no effect on root parameters probably due to the high P values in the soil. The smaller values for soil P caused by diammonium phosphate, relatively to triple superphosphate, had no negative effect on root parameters, P uptake, or dry matter yield of 26-days old maize plants. Therefore, in absence of water deficit, addition of lime and P fertilizers over the soil surface improves the initial growth of maize plants.